Analisis Tekstual Dan Kontekstual Hadis Tentang Adab Peserta Didik Dalam Kitab Ta’limul Muta’alim - Nanang Qosim; Nurul Hidayah; M Ali Irfan (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2022)
Good behavior between students and educators in the learning process will positively impact the interaction of community life. In this study, the researcher examines the hadith about students' etiquette in the Ta'limul Muta'alim book textually and contextually. This study aims to analyze textually and contextually the hadith about students' etiquette in the Ta'limul Muta'alim book. The method used is textual and contextual interpretation. And the form of this research is descriptive qualitative. The first thing to do is reduce the data, then present the data, draw conclusions and verify. As for the results of the research that the researcher obtained regarding the textual analysis of the hadith About Student Ethics In the Ta'limul Muta'alim Book, the adab that a student must possess are: solemn to the teacher, Tawadhu ', Respect for elders. And contextually the hadith is the cause of not entering knowledge, the importance of glorifying knowledge, the danger of being arrogant, placing oneself between pride and inferiority, and the importance of respecting older people.